Syrosingopine and UK5099 synergistically suppress non-small cell lung cancer by activating the integrated stress response - Yiman Li; Yan Song; Zhijing Shi; Huijie Hou; Yang Yu; Fei Pan; Jinlu Ji; Zhe Chen (Cell Death and Disease, 2024)
Abstract Non-small cell lung cancer (NSCLC) presents a global health challenge due to its low five-year survival rates, underscoring the need for novel therapeutic strategies. Our research explored the synergistic mechanisms of syrosingopine and UK-5099 in treating NSCLC. In vitro experiments showed that the combination of syrosingopine and UK-5099 significantly synergized to suppress NSCLC proliferation. Further experiments revealed that this combination induced cell cycle arrest and promoted apoptosis in NSCLC cells. In vivo experiments demonstrated that the combination of syrosingopine and UK-5099 markedly inhibited tumor growth. Mechanistic studies revealed that this drug combination promoted mitochondrial damage by inducing lactate accumulation and oxidative stress. Additionally, the combination triggered an integrated stress response (ISR) through the activation of heme-regulated inhibitor kinase (HRI). Importantly, our findings suggested that the synergistic suppression of NSCLC by syrosingopine and UK-5099 was dependent on ISR activation. In summary, our study proposed a promising therapeutic approach that involved the combination of Syrosingopine and UK-5099 to activate ISR, significantly hindering NSCLC growth and proliferation.